1989
DOI: 10.1093/nar/17.3.1103
|View full text |Cite
|
Sign up to set email alerts
|

Organization and expression of the COX6 genetic locus inSaccharomyces cerevisiae: multiple mRNAs with different 3' termini are transcribed from COX6 and regulated differentially

Abstract: COX6 and its surrounding genetic locus have been characterized for the yeast Saccharomyces cerevisiae. Flanking genes are found closely spaced upstream and downstream of COX6. The upstream gene and COX6 are transcribed from opposite strands and are separated by no more than 300 bp. COX6 is transcribed into three different size classes of mRNA (1000b, 830b, and 700b) differing in length in their 3' untranslated regions. All three classes of mRNAs are found on polysomes and, hence, are most likely translated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Strain JM43GD6 was constructed as follows. The COX6 gene in JM43 was disrupted by use of the plasmid pVISt3 (28), which is derived from pUC19. The URA3 gene was inserted into the HindIII site that is within the COX6 coding region on pVISt3 and the resulting plasmid was used to transform JM43 by the lithium acetate procedure (29).…”
Section: Methodsmentioning
confidence: 99%
“…Strain JM43GD6 was constructed as follows. The COX6 gene in JM43 was disrupted by use of the plasmid pVISt3 (28), which is derived from pUC19. The URA3 gene was inserted into the HindIII site that is within the COX6 coding region on pVISt3 and the resulting plasmid was used to transform JM43 by the lithium acetate procedure (29).…”
Section: Methodsmentioning
confidence: 99%
“…Insofar as the SNFJ gene product is a protein kinase (5), it is possible that SNFJ exerts its effect on SUC2 and other glucose-repressible genes through phosphorylation of the SSN6 gene product or other regulatory factors. address the question, we studied COX6, (25,26) and CYCI (11), the genes that encode cytochrome c oxidase subunit VI and iso-1-cytochrome c, respectively. Previous studies demonstrated that the transcription of both genes is glucose repressible in conjunction with the product of the HAP2 gene (11,23).…”
mentioning
confidence: 99%
“…Three hours following the shift, poly(A)+ RNA was prepared and Northern (RNA) blot analysis was conducted. The blots were hybridized with probes specific for the yeast actin gene (a nonresponding control), ORF-U (a divergently transcribed gene flanking COX6 upstream), or COX6 and ORF-D (a gene flanking COX6 downstream) (26). In the SNFI+ strain, both COX6 and ORF-U showed marked derepression (Fig.…”
mentioning
confidence: 99%
“…One class of S. cerevisiae genes that is now being subjected to intense investigation is that which encodes the mitochondrial respiratory proteins, particularly cytochrome c (13,14,19), cytochrome c oxidase (4,35,43,44,51,52), and coenzyme Q cytochrome c reductase (5,22,26). The intracellular level of each of these respiratory proteins is affected by carbon source (i.e., glucose repression) (30), oxygen tension (18), and heme availability (48).…”
mentioning
confidence: 99%